Applied problems of penetration of sedimentary rocks - Zotsenko , Mykola; Vynnykov, Yuriy; Novokhatniy, Valeriy; Zyma , Oleksandr; Aniskin , Aleksej (Academic journal Industrial Machine Building Civil Engineering, 2023)
A number of topical applied problems on studying the physical and mechanical characteristics of sedimentary rocks using the already sufficiently tested high-speed penetration method are considered, such as: the influence of tip sizes on the value of the static probing index of sands; the influence of the surface quality of conical tips on the results of penetration and probing; improvement of the tip for penetrating rocks with anisotropic properties. New practical possibilities of using the equations of the relationship between the physical properties of rocks and their mechanical parameters, in particular, the specific resistance to penetration or the penetration index, to generalize the results of experiments are shown.
Keywords: sedimentary rock; penetration; penetration tip; penetration index; specific penetration resistance; relationship; rock skeleton density; anisotropy